Integrating Fish Farm Effluents with Mineral Fertilization and Their impacts on Growth, Yield, and Fruit Yield Quality of Squash Plants - Almadini, Abdulrahman M. (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
An open field split plot experiment was conducted using a complete randomized block design with 3 replicates at Research and Training Station of KFU, KSA, aiming to evaluate the effects of integrating various irrigation water types (IWT) of fish farm effluents (shrimp (SW), catfish (CatW), carp (CarW), tilapia (TW), and their mixture (MiW)) and normal well water (NW, control) with different rates of applied mineral NPK fertilizer (MF, 0 (control), 25, 50, and 100 kg ha-1) on growth (plant height, fourth leaf area, and dry leaves weight), yield (fruit no/plant, fruit weight, yield, marketable fruit ratio, and firmness), and yield quality (total soluble solids, total acidity, ascorbic acid, and acid-sugar ratio) traits of squash plants (Cucurbita pepo L., c.v. Agro top). The IWT and MF treatments occupied the main and sub main plots, respectively. Obtained results revealed that there were significant differences between treatments and their interactions. The values of treatments irrigated with fish farm effluents and fertilized with MF were significantly higher than those of controls. The best values were generally under the treatment of MiW and 50 kg ha-1 MF rate. Such results suggest the reliable use of these effluents as non-conventional irrigation water and their environmental, economic, and social values. Their utilization as irrigation water will intensify surface and underground freshwater sustainability, particularly in water scarce countries, as KSA. Also, their use promotes agricultural production, contributing to food security. Finally, further investigations to evaluate their impact on other plants and on soil health and quality are recommended. Some agricultural extension programs are required to enhance the perception of farmers and end users toward their reliable and efficient use as alternative irrigation water.